2006
DOI: 10.1007/bf03393037
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of Relational Matching to Sample in Children: A Direct Replication

Abstract: The ability of preschool age children to perform generalized relational matching to sample tasks with and without an overt mediating stimulus was examined. This experiment was a direct replication of a study by Lowenkron (1984) and examined a behavioral model relevant to complex human behavior that he later came to call joint control. Children were trained to code two-dimensional stimuli with the help of a handheld mediating stimulus. They were later tested for generalization of relational matching to sample w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…The results from the high‐verbal group are consistent with previous research demonstrating that the response products of mediating behavior can provide supplemental sources of stimulus control in MTS performance for rats (e.g., Laties et al, ), pigeons (e.g., Sidman, ), monkeys (e.g., Hodos et al, ), children (Parsons et al, ), and college students (e.g., Santos, Ma, & Miguel, ). In addition, the current study replicates and extends previous research on joint control that showed disrupting mediating verbal behavior impairs performance (e.g., Clough et al, ; DeGraaf & Schlinger, ; Gutierrez, ; Lowenkron, ; Sidener & Michael, ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results from the high‐verbal group are consistent with previous research demonstrating that the response products of mediating behavior can provide supplemental sources of stimulus control in MTS performance for rats (e.g., Laties et al, ), pigeons (e.g., Sidman, ), monkeys (e.g., Hodos et al, ), children (Parsons et al, ), and college students (e.g., Santos, Ma, & Miguel, ). In addition, the current study replicates and extends previous research on joint control that showed disrupting mediating verbal behavior impairs performance (e.g., Clough et al, ; DeGraaf & Schlinger, ; Gutierrez, ; Lowenkron, ; Sidener & Michael, ).…”
Section: Discussionsupporting
confidence: 89%
“…By contrast, Horne and Lowe () and Lowenkron (), who base their positions on Skinner's () analysis of verbal behavior, argue that overt and covert verbal and nonverbal mediating behaviors play an important role in the development of equivalence classes, relational frames, and emergent relations. In support of their view, several studies have demonstrated a participant's self‐verbal behavior can affect performance on various complex tasks (e.g., DeGraff & Schlinger, ; Greer & Longano, ; Horne, Lowe, & Randle, ; Lowenkron, , ; Miguel, Petursdottir, Carr, & Michael, ; Randell & Remington, ; Sidener & Michael, ; Wulfert, Dougher, & Greenway, ).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Participants were seven typically developing 3-6-year-old children, four boys and three girls. Prior research (Ferraro, Francis, & Perkins, 1971;Sidener & Michael, 2006) indicated that children of this age are unlikely to already possess the mediating repertoire supposedly required to perform DMTS. Sessions were conducted with the experimenter and participant seated at tables located in quiet rooms.…”
Section: Participants Setting and Materialsmentioning
confidence: 99%
“…2013; Lowenkron, 1984;Sidener & Michael, 2006). An example is tacting the sample stimulus when it is presented and then echoing the name during the delay until the comparison stimuli are presented.…”
mentioning
confidence: 99%